Employee silence and burnout in India: the mediating role of emotional intelligence. Issue 4 (30th April 2019) - Srivastava, Shalini; Jain, Ajay K.; Sullivan, Sherry
Abstract : Purpose: Although considerable research has been completed on employee voice, relatively few studies have investigated employee silence. The purpose of this paper is to examine the relationship between employee silence and job burnout as well as the possible mediating role of emotional intelligence (EI) on the silence-burnout relationship. Design/methodology/approach: This paper reports the findings of an empirical study based upon the survey of 286 managers working in four different states in India. Correlational and mediated regression analyses were performed to test four hypotheses. Findings: Contrary to findings from studies conducted in Western countries in which employee silence was positively related to undesirable work outcomes, in this study, employee silence was negatively related to job burnout. Additionally, results indicated that the relationship between employee silence and job burnout was mediated by EI. These findings suggest the importance of considering country context and potential mediating variables when investigating employee silence. Practical implications: This study demonstrates how Indian employees may strategically choose employee silence in order to enhance job outcomes. Originality/value: This study is one of the few efforts to investigate employee silence in a non-western country. This is first study that has examined the role of EI as a mediating variable of the relationship between employee silence and job burnout in India.